WHITE PANICLE3, a Novel Nucleus-Encoded Mitochondrial Protein, Is Essential for Proper Development and Maintenance of Chloroplasts and Mitochondria in Rice - Li, Hongchang; Ji, Guobiao; Wang, Yun; Qian, Qian; Xu, Jichen; Sodmergen,; Liu, Guozhen; Zhao, Xianfeng; Chen, Mingsheng; Zhai, Wenxue; Li, Dayong; Zhu, Lihuang (Frontiers in Plant Science, 2018)
Mitochondria and chloroplasts are interacting organelles that play important roles in plant development. In addition to a small number proteins encoded by their own genomes, the majority of mitochondrial and chloroplast proteins are encoded in the cell nucleus and imported into the organelle. As a consequence, coordination between mitochondria, chloroplasts, and the nucleus is of crucial importance to plant cells. Variegated mutants are chloroplast-defective mutants and are considered to be ideal models for studying the intercommunication between these organelles. Here, we report the isolation of WHITE PANICLE3 (WP3), a nuclear gene involved in variegation, from a naturally occurring white panicle rice mutant. Disrupted expression of WP3 in the mutant leads to severe developmental defects in both chloroplasts and mitochondria, and consequently causes the appearance of white-striped leaves and white panicles in the mutant plants. Further investigation showed that WP3 encodes a protein most likely targeted to mitochondria and is specifically expressed in rice panicles. Interestingly, we demonstrate that the recessive white-panicle phenotype in the wp3 mutant is inherited in a typical Mendelian manner, while the white-striped leaf phenotype in wp3 is maternally inherited. Our data collectively suggest that the nucleus-encoded mitochondrial protein, WP3, plays an essential role in the regulation of chloroplast development in rice panicles by maintaining functional mitochondria. Therefore, the wp3 mutant is an excellent model in which to explore the communication between the nucleus, mitochondria, and chloroplasts in plant cells.